2011
DOI: 10.1126/science.1207339
|View full text |Cite
|
Sign up to set email alerts
|

RNA Mimics of Green Fluorescent Protein

Abstract: Green fluorescent protein (GFP) and its derivatives have transformed the use and analysis of proteins for diverse applications. Like proteins, RNA has complex roles in cellular function and is increasingly used for various applications, but a comparable approach for fluorescently tagging RNA is lacking. Here we describe the generation of RNA aptamers that bind fluorophores resembling the fluorophore in GFP. These RNA-fluorophore complexes create a palette that spans the visible spectrum. An RNA-fluorophore com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
1,420
3
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,149 publications
(1,476 citation statements)
references
References 43 publications
28
1,420
3
3
Order By: Relevance
“…The aptamers were selected on the basis of their brightness with respect to GFP to ensure the visual detection of the target. 24 Successful multiplexing of target detection proved the potential of relay PCR to generate multiple signals with aptamers having distant emission spectra (Supporting Information Table S2). …”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aptamers were selected on the basis of their brightness with respect to GFP to ensure the visual detection of the target. 24 Successful multiplexing of target detection proved the potential of relay PCR to generate multiple signals with aptamers having distant emission spectra (Supporting Information Table S2). …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…24 This RNA−fluorophore complex displays fluorescence properties similar to GFP, but unlike most fluorescent proteins it is resistant to photobleaching. Further, DFHBI is fluorescent only upon binding to RNA, and it is not activated by the other components in the reaction.…”
mentioning
confidence: 99%
“…Fig. 3 a FACS analysis of E. coli cells from rounds 1, 3, and 6. b Proposed secondary structures of aptamers ZT-26 and ZT-324, mutation domains are indicated in gray shadow, and Spinach structure comes from Paige et al (2011 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jaffrey and colleagues have engineered an RNA aptamer, denoted ''Spinach,'' that mimics the function of green fluorescent protein (GFP): when bound with 3,5-difluoro-4-hydroxybenzylidene imidazolinone (DFHBI), Spinach becomes brightly fluorescent. It has been reported that Spinach/DFHBI displays fluorescence properties similar to GFP (*50 % brightness of EGFP), and therefore, this system represents a useful tool to examine RNA activities in cells (Paige et al 2012(Paige et al , 2011Song et al 2014;. The same group has also engineered another aptamer, named ''Broccoli,'' that can also bind and activate DFHBI (Filonov et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…If inserted to 3′ end of RNA molecules including lncRNAs, the localization of target RNAs can be revealed upon addition of the fluorophore to the cell. One RNA mimic of eGFP referred to as Spinach binds DFHBI [(Z)‐4‐(3,5‐difluoro‐4‐hydroxybenzylidene)‐1,2‐dimethyl‐1H‐imidazol‐5(4H)‐one] was inserted to the 3′ end of 5S rRNA and successfully revealed its subcellular distribution 42. Therefore, the GFP RNA mimics can be applied to lncRNA research so as to enhance and simplify the attempt to map subcellular localization of these transcripts and how they might change in cancer disease.…”
Section: Methods Used To Localize Lncrnas Inside the Cellmentioning
confidence: 99%